Pengaruh Akuntabilitas Pelayanan Terhadap Kepuasan Pelanggan pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jayapura - Menik Tiwikarti; Yundy Hafizrianda; Arius Kambu (Universitas Cenderawasih, 2021)
The Purpose of this study is to analyse the servise satisfaction at Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jayapura and how is the influence of servise quality , namely physical evidence, reliability, responsiveness, assurance and empathy to public service satisfaction. The population of this study is the population of users of population Administration services at the Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jayapura. Testing samples of 85 people. The sample method used was purposive sampling. Data collection was carried out by direct surveys, interviews and also by distributing questionnares. Empirical hypothesis testing using Multiple Regression. The result showed that the services had been implemented in accordance with the established Standart Operating Prosedures, but there is a need for improvements in facilities, infrastructure and facilities for vicitors or service users. The five observed service quality, physical evidence, reliability, responsiveness, assurance and empathy have apositif and significant effect on service satisfaction. This proves that if the five observed variables are further improved, it will increase public service satisfaction at the Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jayapura